Roles of Cysteine Proteases Cwp84 and Cwp13 in Biogenesis of the Cell Wall of Clostridium difficile - de la Riva, Lucía (American Society for Microbiology, 2011)
Clostridium difficile expresses a number of cell wall proteins, including the abundant high-molecular-weight and low-molecular-weight S-layer proteins (SLPs). These proteins are generated by posttranslational cleavage of the precursor SlpA by the cysteine protease Cwp84. We compared the phenotypes of C. difficile strains containing insertional mutations in either cwp84 or its paralog cwp13 and complemented with plasmids expressing wild-type or mutant forms of their genes. We show that the presence of uncleaved SlpA in the cell wall of the cwp84 mutant results in aberrant retention of other cell wall proteins at the cell surface, as demonstrated by secretion of the proteins Cwp66 and Cwp2 into the growth medium. These phenotypes are restored by complementation with a plasmid expressing wild-type Cwp84 enzyme but not with one encoding a Cys116Ala substitution in the active site. The cwp13 mutant cleaved the SlpA precursor normally and had a wild-type-like colony phenotype. Both Cwp84 and Cwp13 are produced as proenzymes which are processed by cleavage to produce mature enzymes. In the case of Cwp84, this cleavage does not appear to be autocatalytic, whereas in Cwp13 autocatalysis was demonstrated as a Cys109Ala mutant did not undergo processing. Cwp13 appears to have a role in processing of Cwp84 but is not essential for Cwp84 activity. Cwp13 cleaves SlpA in the HMW SLP domain, which we suggest may reflect a role in cleavage and degradation of misfolded proteins at the cell surface.